TINJAUAN HUKUM PP 94 TAHUN 2021 TENTANG DISIPLIN PNS DI LINGKUNGAN PEMERINTAH KABUPATEN BOGOR - Mohamad Nurjen; Sudarto (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
This study aims to analyze the implementation of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline (PP 94/2021) within the Bogor Regency Government. As part of the bureaucratic reform agenda, PP 94/2021 replaces the previous regulation (PP No. 53 of 2010) by emphasizing the principles of legal certainty, justice, and proportionality in civil servant discipline management. This research employs a normative legal method with a conceptual and statutory approach, supported by document-based data on civil servant disciplinary violations. The findings indicate that the implementation of PP 94/2021 in Bogor Regency faces procedural and bureaucratic obstacles, with 57.6% of violation cases in the first half of 2025 remaining unresolved. The complexity of the existing Standard Operating Procedures (SOP), limited human resources, and suboptimal utilization of digital systems are identified as key challenges. Additionally, administrative law issues arise from the policy of cutting Additional Income Allowances (TPP) for sanctioned civil servants, which, although legally valid, may be disproportionate if not supported by fair and transparent technical regulations. This study highlights the importance of harmonizing legal norms with bureaucratic realities to ensure that civil servant discipline enforcement is effective, equitable, and accountable.